Young Investigator: Michelle J Yoo. (March 2011) - Yoo, Michelle J
Supervisor''s supporting comments I have always been impressed with Michelle''s ability to conduct research in an independent and yet highly effective manner. Part of her research in my group has examined the use of affinity columns to examine drug––protein binding with serum proteins, such as human serum albumin. This work is extremely important to the fields of pharmaceutical chemistry and clinical chemistry in providing the data needed for the development of new drugs or in the optimization of treatments for patients with new, or existing, drugs. Another topic that Michelle has examined in her research is the use of new supports based on monolithic materials and ultrafast-extraction methods for affinity-based separations of biological samples and high-throughput screening of drug––protein binding. She was the lead author on a review written on this topic and also has several research publications related to this area of work. During her graduate studies, Michelle has emerged as a real leader in my group. She has excellent people and communication skills and is highly motivated in her pursuit of an advanced degree in analytical chemistry and bioanalysis. I have extremely high expectations for her in the future as she continues her career. Nominated by: David S Hage, University of Nebraska, Department of Chemistry, Hamilton Hall 704, Lincoln, NE 68588, USA